Design of Islamic Religious Education (PAI) Learning Management in Integrated Islamic Schools - Andri Kusmayadi Andri; Yosep Farhan Dafik Sahal; Fiqih Fazryansyah; Bambang Samsul Arifin (EDUTEC : Journal of Education And Technology, 2024)
This article explores the design of Islamic Religious Education (PAI) learning management in Integrated Islamic Schools (SIT). With a literature research approach, this article identifies critical aspects in the direction of PAI learning, which includes planning, implementation, and evaluation. Important aspects of planning include setting learning objectives that focus on developing aspects of religion, morals, and character of learners; relevant and contextual curriculum analysis; development of integrative learning materials; varied and interactive learning methods; use of technology in learning; and comprehensive evaluation and assessment. The implementation of education at SIT emphasizes the integration of Islamic values in the learning process, effective use of media, and active involvement of students. The monitoring and evaluation phase involves assessing knowledge, worship practices, attitudes and behaviors, as well as student projects and assignments. The article also highlights the importance of parent and community involvement and the professional development of PAI teachers. In conclusion, the design of PAI learning management at SIT requires a holistic approach that integrates pedagogical, technological, and community aspects to create a compelling and conducive learning environment for the spiritual development and Islamic character of learners